2021
DOI: 10.1177/09636897211034464
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal Transplantation of Autologous and Allogeneic Bone Marrow-Derived Mesenchymal Stem Cells in Dogs

Abstract: The route used in the transplantation of mesenchymal stem cells (MSCs) can directly affect the treatment success. The transplantation of MSCs via the intrathecal (IT) route can be an important therapeutic strategy for neurological disorders. The objective of this study was to evaluate the safety and feasibility of the IT transplantation of autologous (Auto-MSCs) and allogeneic (Allo-MSCs) bone marrow mesenchymal stem cells (BM-MSCs) in healthy dogs. Based on neurodisability score, cerebrospinal fluid (CSF) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 61 publications
(86 reference statements)
0
8
0
Order By: Relevance
“…Recent clinical and preclinical studies have established the safety of intrathecal MSC transplantation. Intrathecal infusion of 1.5 × 10 6 BM-MSCs in dogs did not produce any differences in the number of nucleated cells or the levels of pro-MMP2 or MMP9 in the CSF before or after transplantation and MRI analysis one year post-transplantation did not reveal alterations in the brain [ 25 ]. Similarly, intrathecal infusion of 1.0 × 10 6 BM-MSCs in horses did not produce changes in CSF cell count or pro-MMP2 level or cause signs of the neurological disorder [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent clinical and preclinical studies have established the safety of intrathecal MSC transplantation. Intrathecal infusion of 1.5 × 10 6 BM-MSCs in dogs did not produce any differences in the number of nucleated cells or the levels of pro-MMP2 or MMP9 in the CSF before or after transplantation and MRI analysis one year post-transplantation did not reveal alterations in the brain [ 25 ]. Similarly, intrathecal infusion of 1.0 × 10 6 BM-MSCs in horses did not produce changes in CSF cell count or pro-MMP2 level or cause signs of the neurological disorder [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rate of CSF secretion equals that of its removal, so obstruction of flow allows fluid accumulation and causes enlargement of the cavity in front of the blockage. Although several studies have demonstrated the feasibility of intrathecal transplantation of MSCs, the influence on CSF flow has not been carefully examined [ 22 , 24 , 25 ]. MSCs are known for their tendency to self-assemble and spontaneously form aggregates in suspensions [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…For clinical strategies, the main concept is the morphological and functional reestablishment of bone tissue. Current therapeutic treatments for bone tissues include bone transplantation (e.g., autogenous bone or allogeneic bone), (Behrend et al, 2016), bone substitution materials (e.g., titanium plate), (Diwu et al, 2020), stem cell transplantation (e.g., bone marrow stem cells, bMSCs), (Benavides et al, 2021), biological agents (e.g., growth factors), (Kitaura et al, 2022), gene therapy, (Gao et al, 2022), distraction osteogenesis, (Qi et al, 2009), and barrier membrane to guide bone regeneration. (Han et al, 2018) The purposes of applying bone filling materials in guided bone regeneration (GBR) procedures are: 1) supporting the barrier film to avoid collapse; (Cox et al, 2022) 2) scaffolding for new bone to grow in from the receptive area; (Roseti et al, 2017) 3) stimulating the growth of new bone from the receptive area; (Robling and Bonewald, 2020) 4) resisting to surface soft tissue pressure; (Hao et al, 2022) 5) protecting the new bone mass and avoiding its absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of route of administration, in nearly all published studies, allogeneic MSCs (alloMSCs) were used, requiring concomitant treatment with harsh immunosuppressant drugs to prevent the rapid immunorejection of transplanted cells [48,49]. Except for several rodent studies [35,40,50], there remains scant information on the potential utility of autologous MSCs (autoMSCs) which lack immunogenicity. The ability of autoor alloMSCs to improve recovery in chronic stroke models remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%